Effect of concentration starter and fermentation time on the quality of yoghurt drink from buffalo milk. (May 2020) - Sinamo, K N; Hasan, F; Hasanah, U
Abstract: Generally yogurt drinks are made from cow's milk, whereas buffalo milk has a higher nutrition value than cow's milk. The objective of this study was to produce yoghurt drinks from buffalo milk and determine proximate composition and sensory quality of the product based on starter concentration and fermentation time. The experiment was carried out using a completely randomized design of factorial patterns consisting two factors, i.e. starter concentration (3, 5 and 10%) and fermentation time (8 and 12 hours). The results of proximate analysis obtained showed starter concentration had significant effect on moisture, fat, protein and carbohydrate contents. While fermentation time had significant effect on fat and protein contents. The sensory evaluation result showed significant differences among the yoghurt drink samples. Sample F (10% starter concentration and 12 hours fermentation time) had the highest scoore in sensory atributes.